2015
DOI: 10.1007/s11356-015-5306-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration characteristics in different land uses and response of soil organic carbon to biochar addition in high-latitude agricultural area

Abstract: The farmland tillage practices changed the soil chemical properties, which also impacted the soil respiration (R s ) process and the soil carbon conservation. Originally, the farmland in northeast China had high soil carbon content, which was decreased in the recent decades due to the tillage practices. To better understand the R s dynamics in different land use types and its relationship with soil carbon loss, soil samples at two layers (0-15 and 15-30 cm) were analyzed for organic carbon (OC), total nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…30,43 Sigua et al, 44 conducted a field study using switch grass biochar and found that biochar additions to soil increased N immobilization and decreased in total inorganic N in soils due to the wide C/N ratio of switch grass. These researchers also observed a significant increase in cumulative and net CO 2 flux implying biochar simulated switchgrass mineralization and accelerated decomposition of resident soil C. 44,45 Similar observations such as increased respiration rates have been recently reported; 46 however, Jones et al 47 suggested that increased CO 2 evolution immediately after biochar addition partially originates from the emission of inorganic C within biochar itself. Therefore, the influence of biochar on N immobilization needs to be further studied with focus on the bioavailable C and direct effects of biochar on microbial activity.…”
Section: Biochar and Soil Nutrient Transformations Nitrogensupporting
confidence: 59%
“…30,43 Sigua et al, 44 conducted a field study using switch grass biochar and found that biochar additions to soil increased N immobilization and decreased in total inorganic N in soils due to the wide C/N ratio of switch grass. These researchers also observed a significant increase in cumulative and net CO 2 flux implying biochar simulated switchgrass mineralization and accelerated decomposition of resident soil C. 44,45 Similar observations such as increased respiration rates have been recently reported; 46 however, Jones et al 47 suggested that increased CO 2 evolution immediately after biochar addition partially originates from the emission of inorganic C within biochar itself. Therefore, the influence of biochar on N immobilization needs to be further studied with focus on the bioavailable C and direct effects of biochar on microbial activity.…”
Section: Biochar and Soil Nutrient Transformations Nitrogensupporting
confidence: 59%
“…4 ). However, denitrification rate tended to be more consistency with respiration rate than that of nitrification rate, for the reason that denitrification and respiration are carbon consuming processes 23 63 64 65 . As can be seen from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Between 52°N and 40°S, SOC was negatively correlated with soil temperature. In these tropical and temperate zones, the soil temperature is the dominant limiting factor of soil respiration (SOC decomposition), whereas photosynthesis (SOC formation) is limited by multiple factors, including light, CO 2 concentration, water stress, and nutrient availability (Stockmann et al, 2013;Ouyang et al, 2016). Therefore, this negative correlation was most likely due to the increasing soil respiration with increasing temperature (Post et al, 1982;Ghosh et al, 2016).…”
Section: Location-and Scale-specific Correlations Between Soc and Tem...mentioning
confidence: 99%